Design Processes and Tools as Oppression? Rethinking our Design Practice for more Just Design Outcomes - Manuhuia Barcham (Diseña, 2023)
Our design processes and tools matter, as our design is always shaped by the processes and tools that we use. Context necessarily shapes the content of our design processes and tools. But, without paying attention to the content emerging from that context, the use of these tools and processes may become oppressive. In the wake of colonialism, the un-reflexive use of design tools and processes underpinned by Western conceptual ideas and schema can lead to oppression for design with non- Western or Indigenous peoples. Even tools and processes designed with a supposedly liberatory intent, such as promoting democratic practice or equality, can lead to oppression in their un-reflexive use. Looking at two experiences from my design practice with my own hapū (clan), this article explores the ways in which ideas of democratic participation and equality raised in these two design spaces could function in an oppressive way to cause a form of violence against our traditional lifeworld. This article proposes some ways in which this aspect of design might be modified to help lead to more just design outcomes, through a more reflective and intentional approach when choosing and applying the design tools and processes we use in our design practice.